Penyuluhan dan Pemeriksaan Kesehatan Gigi untuk Meningkatkan Kesadaran Kesehatan Mulut pada Anak Sekolah Dasar - Rezqiqah Aulia Rahmat; Nurhaedah Nurhaedah; Eko Prastyo (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Children's dental health is a crucial foundation for their future growth, development, and quality of life. The high caries rate among elementary school children in Indonesia indicates a low level of awareness about maintaining dental hygiene from an early age. This Community Service (PKM) activity aims to improve students' understanding of dental and oral health through education, toothbrushing demonstrations, educational games, and direct dental health examinations. The activity was conducted with 20 students in grades I–VI at an elementary school. Results showed a 20% increase in student knowledge and the identification of various dental problems such as caries, plaque, and mild gingivitis. This program has had a positive impact on increasing oral health awareness in children and serves as a foundation for ongoing development.